Perbedaan Pengaruh Birth Ball dan Hypnobirthing Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif di Wilayah Kerja Puskesmas Sei Langkai - Nurfaida Kamarullah; Mona Rahayu Putri; Ditte Ayu Suntara (Jurnal Kesehatan Amanah, 2024)
Labor pain is needed to detect uterine contractions during childbirth, but pain also increases the mother's anxiety and fear during the birth process. Management of labor pain that can be done is birth ball therapy and hypnobirthing. The aim is to determine the difference in the effect of Birth Ball therapy and Hypnobirthing on reducing labor pain in the I phase active for maternity women in the working area of Puskesmas Sei Langkai Batam City. The design of this research is Quasi experimental with a Two-group interrupted time series design. Respondents were divided into 16 experimental groups and 16 control groups. The sampling technique used was purposive sampling and data collection using observation sheet. The results of the study were (p = 0.305 > 0.05), meaning there was no significant difference between the birth ball and hypnobirthing groups in reducing pain, (p = 0.003 < 0.05) meaning there is a significant difference between the pre-test and post-test scores on pain reduction, (p = 0.718 > 0.05) meaning there is no interaction between group (birth ball and hypnobirthing) and score (pre-test and post-test) on reducing pain. Based on these results, it can be concluded that measurement time (pre-test and post-test) has a significant effect on pain scores, but there is no significant effect between different groups, and there is no significant interaction between group and time on reducing labor pain.